2018
DOI: 10.2807/1560-7917.es.2018.23.41.1700772
|View full text |Cite
|
Sign up to set email alerts
|

Divergent approaches in the vaccination of recently arrived migrants to Europe: a survey of national experts from 32 countries, 2017

Abstract: BackgroundMigrants within the European Union and European Economic Area (EU/EEA) may be underimmunised and lack documentation on previous vaccinations. We investigated approaches to vaccination in recently arrived adult and child migrants, and guideline availability and implementation. Methods: Between March and May 2017, a national vaccination expert from every EU/EEA country and Switzerland completed an electronic questionnaire. We used descriptive analyses to calculate percentages, and framework analysis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 20 publications
(28 reference statements)
0
44
0
Order By: Relevance
“…These concerns were also shared in a survey among vaccination experts of 32 EU member states. 53 The respondents underpinned the need for EU-level guidelines on vaccination and indicated that vaccination should be offered primarily at the point of entry or at the holding level (eg, reception centres and migrant camps). Accordingly, future actions should focus on a systemic and tailored approach to address these challenges and provide adequate protection for migrants and refugees.…”
Section: Viewpointmentioning
confidence: 99%
“…These concerns were also shared in a survey among vaccination experts of 32 EU member states. 53 The respondents underpinned the need for EU-level guidelines on vaccination and indicated that vaccination should be offered primarily at the point of entry or at the holding level (eg, reception centres and migrant camps). Accordingly, future actions should focus on a systemic and tailored approach to address these challenges and provide adequate protection for migrants and refugees.…”
Section: Viewpointmentioning
confidence: 99%
“…The high burden of vaccine-preventable diseases among migrant children compared with non-migrant children underscores the need for timely vaccination in this vulnerable population [76][77][78][79][80]. Despite the recommendations for age-appropriate vaccinations for migrant children with absent or uncertain immunization records, studies have shown that migrants in the EU are not up to date on vaccinations [81,82]. A cohort study from Denmark showed that 30% of asylum-seeking children were not up to date on vaccinations in accordance with national guidelines [17].…”
Section: Vaccine-preventable Diseasesmentioning
confidence: 99%
“…The high burden of vaccine-preventable diseases among migrant children compared with non-migrant children underscores the need for timely vaccination in this vulnerable population [76][77][78][79][80]. Despite the recommendations for age-appropriate vaccinations for migrant children with absent or uncertain immunization records, studies have shown that migrants in the EU are not up to date on vaccinations [81,82]. A cohort study from Denmark showed that 30% of asylum-seeking children were not up to date on vaccinations in accordance with national guidelines [17].…”
Section: Vaccine-preventable Diseasesmentioning
confidence: 99%